Principles of formation of individual training programs taking into account morphological and biochemical parameters of rowing and canoeing - Maslova, I. N. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
When considering the relevant ways to develop customized training programs of preparation of highly skilled rowers on kayaks and canoes by the criteria of their efficiency to load of the competitive exercises are the morpho-functional and biochemical indicators. The task was to systematize the ways of developing individual training programs taking into account the above parameters. At their introduction in training process it is necessary to use model technologies of all leading components of long-term sports career.